Territorialidades no agreste paraibano: as mulheres e suas práticas na rede borborema de agroecologia - Santos, Tainá Maria de Oliveira (2023)
The inclusion of rural women in public food production policies in Brazil has been the result of peasant organization and mobilizations in the streets, in the struggle for recognition of their work and better living conditions in the countryside. In Paraíba, the Borborema Agroecology Network has boosted women's organization and work with agroecology in food and cotton production. In the process, the identity of peasant agroecological producers has been strengthened through access to public policies and the constitution of autonomy in work and in the management of common goods in their territories. In order to understand how agroecology influences the daily lives of human beings, this research was based on the contradictory movement of capital production in modern society. In other words, at the same time as economic neoliberalism points to a homogenization of agricultural production via agribusiness, this same mode of production reveals practices, highlighting that peasant women are moving towards overcoming monocultures based on agroecology, and are therefore taking different and alternative paths. With this in mind, our general objective is to analyze the territorialities of women who work in agroecological certification networks in the sustainable production of food and care. With this in mind, our general objective is to analyze the territorialities of women who work in agroecological certification networks in the sustainable production of food and care. To this end, we sought to: a) reveal participatory organic certification as an achievement of the Brazilian peasantry; b) discuss agroecology as a movement that organizes the peasantry; and c) identify the territorialities of peasant women in Borborema. The centrality of the research lies in participant action with a qualitative approach in order to understand social and landscape relations, given that people are inserted in their daily lives, crossed by a culture and a way of life, and thus represent a place based on an identity. In this sense, we have the territorial focus of the Queimadas Settlement, an agrarian space in the Agreste Paraibano Mesoregion and Western Curimataú Microregion, in the rural area of the municipality of Remígio, where the headquarters of the OPAC/SPG Rede Borborema de Agroecologia (Borborema Agroecology Network), considered the first Participatory Guarantee System (SPG) in the state, was founded on July 23, 2013. The results show that in practice, organic agroecological cotton is an experience that has brought peasants closer to the path of participatory certification. The guarantee for all plant and primary production, the certificate and the right to market are strategies for maintaining local diversity in the semi-arid region of Paraiba. The women's life trajectory reveals a rapprochement with handicraft practices such as making brooms from Macambira straw, knowledge of medicinal herbs and an openness to experiences such as exchanges, demonstrations in cities and an interest in socializing. The women of the RBA are mobile, articulate with social movements and work with education, institutional sales and strengthen their listening and popular organization.